Components of sensorimotor adaptation in young and elderly subjects - Bock, Otmar (Experimental brain research, 2005)
Previous studies have found that sensorimotor adaptation to visual distortions is degraded in seniors compared with younger subjects, whereas after-effects on removal of the distortion are age-independent. The latter finding was interpreted as evidence that adaptive recalibration is not affected by old age, and that the observed degradation is therefore due to impairment of strategic control. However, after-effects are not a reliable measure of recalibration, because they can be artificially inflated by perseveration, a characteristic symptom in old age. The present work therefore introduces a test of recalibration which is insensitive to perseveration. Twelve young and twelve old subjects executed center-out pointing movements while visual feedback about their fingertip was either veridical (baseline), 60-deg rotated (adaptation), or absent (after-effect). They also executed tracking movements toward an unpredictably moving object before and after the pointing task. Seniors adapted less than younger subjects but their after-effects were not degraded. More importantly, transfer of adaptation from a pointing to a tracking task was not degraded in seniors. The latter outcome documents, in a more compelling fashion than previous work, that recalibration in the elderly is not impaired, and that the observed deficit of adaptation is therefore most probably because of impaired strategic control. This conclusion is supported by two additional findings: compared with young subjects our seniors performed less well on a cognitive screening test and acquired no explicit knowledge about the nature of the imposed visual distortion.